Pioneering Farmers Value Agronomic Performance of Cover Crops and Their Impacts on Soil and Environment - Peltonen-Sainio, Pirjo; Jauhiainen, Lauri; Mattila, Tuomas J.; Joona, Juuso; Hydén, Tony; Känkänen, Hannu (MDPI AG, 2022)
Cover crops (CCs) have aroused a great deal of interest as a multifunctional measure to improve the sustainability of agriculture. Understanding farmers’ views are important for future farm-scale implementation. A farmer survey was carried out in Finland in 2021 with the aims to gather farmers’ views on agronomic performance of CCs, their environmental impacts and contribution to climate smart agriculture, and understand how farmers’ views on CCs differed depending on farm/farmer characteristics. The farmers’ sample was conventional and organic farms that had selected CCs as a registered measure in 2020. 6493 farmers were invited to answer a questionnaire with 18 statements (a Likert scale, 5 answer choices), and 1130 responded (17.4%). A Cochran–Mantel–Haenszel test was used to measure the strength of the association between ten characteristics of the respondents and 18 statements. Farmers considered CCs to have wide-ranging benefits for soil conditions. Only 21% of farmers agreed that CCs increase the need for nitrogen fertilizer use. 49% of farmers agreed that CCs reduce weed problems. Farmers mostly agreed (ca. 80%) that CCs reduce nutrient leaching and erosion. They were in general more uncertain about CCs’ contribution to climate change mitigation (53% agreed), adaptation (51%), and resilience (58%). In agri-environmental schemes subsidies for use of CCs should aim large-scale implementation with two important target groups: younger farmers (≤50 years) as they were slightly more skeptical than older ones and farmers with less diverse land use as they were more doubtful of benefits provided by CCs
Keywords: cash crop; climate smart agriculture; competition (biology); cover crop; diversification; farming system; land use; soil health